Green Product, Quality, and Price on Interest in Buying Fast Food KFC Palopo City (Study on Consumers Palopo City KFC Fast Food Restaurant ) - M. Risal; Muhammad Aqsa; Mutia Adam (Jurnal Mantik, 2022)
The ability to survive and continue to develop in the competitive world of business must be the top priority in the midst of intense competition with similar products. Creating and implementing green products as well as improving the quality and controlling the prices of the products are part of the company's ability to survive and thrive. This study aims to determine the effect of green products, product quality and product prices on buying interest. Multiple regression analysis was used in this study with a total sample of 85 respondents. The findings of this study indicate that green products, product quality and product prices both simultaneously and partially affect the interest in buying fast food at KFC Palopo City